Complete chloroplast genome of Myracrodruon urundeuva and its phylogenetics relationships in Anacardiaceae family - Rossini, Bruno Cesar [UNESP] (2021)
Continuous exploratory use of tree species is threatening the existence of several plants in South America. One of these threatened species is Myracroduron urundeuva, highly exploited due to the high quality and durability of its wood. The chloroplast (cp) has been used for several evolutionary studies as well traceability of timber origin, based on its gene sequences and simple sequence repeats (SSR) variability. Cp genome organization is usually consisting of a large single copy and a small single copy region separated by two inverted repeats regions. We sequenced the complete cp genome from M. urundeuva based on Illumina next-generation sequencing. Our results show that the cp genome is 159,883 bp in size. The 36 SSR identified ranging from mono- to hexanucleotides. Positive selection analysis revealed nine genes related to photosystem, protein synthesis, and DNA replication, and protease are under positive selection. Genome comparison a other Anacardiaceae chloroplast genomes showed great variability in the family. The phylogenetic analysis using complete chloroplast genome sequences of other Anacardiaceae family members showed a close relationship with two other economically important genera, Pistacia and Rhus. These results will help future investigations of timber monitoring and population and evolutionary studies.